Issues and Problems in Ethical Practices amongst Takaful Agents - Aziz, Nor Aziza Abdul; Ghani, Abdullah Haji Abdul; Shaari, Hasnizam (International Review of Management and Marketing, 2016)
This paper discusses contributing factors pertaining to the ethical behaviour of Takaful agents in Malaysia. Perspective of sales, selling pressure and the level of competitiveness are identified as factors, influencing ethical behaviour of Takaful agents. This study is conducted through focus group and formed a personal interview among branch managers, executives and Takaful agents. It revealed that unethical behaviour is evident among the Takaful agents in meeting the sales target. These factors can be used as a signal for practitioners and Takaful operators in order to avoid unethical practice in dealing with customers. Keywords: Takaful Agents; unethical behaviour; Takaful Industry JEL Classifications: K4, L2